2019
DOI: 10.21926/obm.transplant.1902069
|View full text |Cite
|
Sign up to set email alerts
|

The DPP4 Inhibitor Sitagliptin Increases Active Glp-1 Levels from Human Islets and May Increase Islet Cell Survival Prior to Transplantation

Abstract: Background: One of the goals of clinical islet transplantation is to achieve a single-donor transplant that is dependent on obtaining enough quality  cell mass from one donor pancreas. Human islets are routinely cultured prior to transplantation, and pro-survival factors such as GLP-1 analogues have been reported to maintain  cell mass and survival. Interestingly, human islets may secrete GLP-1 and they also express the enzyme DPP4 that proteolytically cleaves GLP-1 into an inactive form. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Recent evidence in mice genetically engineered to reexpress Gcg has suggested that bioactive and glucoregulatory GLP-1 may be produced in the pancreas. 101 Dipeptidyl peptidase-4 protein expression has been observed in isolated human islets, 102 and GLP-1R antagonism blunts the DPP4i (linagliptin) improvement in mice with Gcg expression restricted to the pancreas, 103 suggesting a potential pancreatic, paracrine circuit to control glycemia. However, further use of these models to reexpress Gcg in the proximal and distal gut demonstrates gut-derived GLP-1 is indeed the dominant site of GLP-1, and pancreas perfusion studies with a DPP4i have demonstrated no impact on glycemia.…”
Section: Dpp4 Inhibitors In Combination With Metforminmentioning
confidence: 99%
“…Recent evidence in mice genetically engineered to reexpress Gcg has suggested that bioactive and glucoregulatory GLP-1 may be produced in the pancreas. 101 Dipeptidyl peptidase-4 protein expression has been observed in isolated human islets, 102 and GLP-1R antagonism blunts the DPP4i (linagliptin) improvement in mice with Gcg expression restricted to the pancreas, 103 suggesting a potential pancreatic, paracrine circuit to control glycemia. However, further use of these models to reexpress Gcg in the proximal and distal gut demonstrates gut-derived GLP-1 is indeed the dominant site of GLP-1, and pancreas perfusion studies with a DPP4i have demonstrated no impact on glycemia.…”
Section: Dpp4 Inhibitors In Combination With Metforminmentioning
confidence: 99%
“…shown that treatment of islets from T2D patients with DPP4 inhibitor sitagliptin led to increased GLP-1 secretion, which was associated with improved β-cell health and survival (Bugliani et al, 2018;Buteau et al, 2004;Campbell et al, 2019;Farilla et al, 2003;Li et al, 2003). As such, we hypothesized that the deletion of intra-islet Dpp4 could prevent the cleavage of GLP-1 by DPP4 within the islet, thus resulting in improved glucose tolerance via the augmented paracrine action on the β-cell.…”
Section: Dpp4 Expressed In Mip-mentioning
confidence: 89%
“…DPP4 inhibition protects beta cells from lipo- and glucotoxicity, 14 , 26 , 78 and improves islet survival in culture. 26 , 78 Intra-islet DPP4, whether endothelial or endocrine cell-derived, may reduce GLP-1 concentrations, limiting the GLP-1 mediated protection of beta cells. As discussed above, DPP4 inhibitors have the potential to increase active GLP-1 concentrations in the local islet microenvironment.…”
Section: Degradation Of Incretins By Intra-islet Dipeptidyl Peptidasementioning
confidence: 99%
“…This finding suggests that sitagliptin, and other DPP4 inhibitors, may preserve healthy beta cell mass during the pre-transplant culture period and increase beta cell survival immediately post-transplant. 78 Finally, DPP4 inhibitors may increase GLP-1 secretion from the remaining alpha cells in T1D, as many T1D patients are identified with residual functional beta cell mass. 83 These patients may benefit from increased active GLP-1 levels local to the beta cell, with potentially less need for exogenous insulin and a reduced risk of hypoglycemia.…”
Section: Degradation Of Incretins By Intra-islet Dipeptidyl Peptidasementioning
confidence: 99%